Perceived stress of COVID-19 pandemic and problematic mobile phone use during quarantine conditions among Chinese adolescents: a mediated moderation model - Jiang, Shuyang; Zhang, Lifan (Frontiers in Psychology, 2024)
The relation between perceived general stress and problematic mobile phone use (PMPU) has been well established. With the outbreak of the coronavirus disease (COVID-19), the present study was designed to examine the associations between perceived stress of COVID-19 as a kind of event-related stress and PMPU, and the mechanisms underlying this relation. Participants were 724 adolescents ranging from 12 to 16 years old (M = 13.28, SD = 1.05) who completed four online questionnaires addressing perceived stress of COVID-19, search for meaning in life, escapism motivation, and PMPU. The results revealed that escapism motivation mediated the relationship between perceived stress of COVID-19 and PMPU. In addition, search for meaning in life played a moderating role between perceived stress of COVID-19 and escapism motivation. These findings extend the literature by addressing how and under what conditions perceived stress of COVID-19 can contribute to PMPU. We discussed the implications for developing targeted intervention programs aimed at reducing PMPU among adolescents.